Mechanical Fetal Simulator for Fetal Doppler Testing - Arum Triwerdani; Syaifudin Syaifudin; Bedjo Utomo; Abdul Basit (Journal of Electronics, Electromedical Engineering, and Medical Informatics, 2022)
The continuous use of fetal Doppler allows for discrepancies in values ​​that lead to misdiagnoses in patients. This study aims to determine the effect of sound source distance on the fetal simulator with the measurement point. The contribution of this research is that the mechanical fetal heart system has 4 distances so that later it can be analyzed whether there is an influence of the location of the sound source on the accuracy of measurements using a fetal simulator. To get the desired distance, a solenoid is used which ends with a pipe of 2 cm, 5 cm, 10 cm, and 50 cm respectively. The solenoid used in the fetal simulator functions as a producer of the fetal heart. There is a rotary switch that functions for solenoid selection, namely 2 cm, 5 cm, 10 cm and 50 cm solenoids. Data collection was carried out on each solenoid and by placing the Doppler probe perpendicular and tilted. On the solenoid with a distance of 50 cm all measurement results exceed the allowable tolerance limit. The results showed that the BPM value of the two Doppler brands did not have a significant difference in value. When measuring fetal Doppler, the largest error value was 2.67%. The results of this study can be used as a reference when conducting an examination